POWER SYSTEM RELIABILITY ANALYSIS FOR DIFFERENT LINE OUTAGE CONDITIONS - Akanksha Priya; Sujit Pani; Dipu Sarkar; Lomi, Abraham (Journal of Sustainable Technology and Applied Science (JSTAS), 2022)
Power System Reliability Assessment is a crucial and significant feature of power system design, planning, and operation. A power system comprises many components that are interconnected in meaningful and rational ways. In the present paper, a simulation is carried out for line outage conditions. In a power system, some of the lines are extremely important. If such a line outage is happening then a cascading failure may occur. This failure leads to grid collapse. So, a power engineer needs to know which line will be more important. In the present work, reliability was done for different line outage conditions to check the importance of the line. This report defines a transmission network, generation system, and load model that can be used to compare the power system of reliability assessment methods. The objective is to estimate the reliability index for improvement of power system reliability analysis for different line outage conditions. The improvement in reliability assessment was evaluated with a reliability index that includes ACCI (Average Customer Curtailment Index), AENS (Average Energy Not Supplied), ASAI (Average Service Availability Index), ASUI (Average Service Unavailability Index), CAIDI (Customer Average Interruption Duration Index), CTAIDI (Customer Total Average Interruption Duration Index), EENS (Expected Energy Not Supplied), SAIDI (System Average Interruption Duration Index), and SAIFI (System Average Interruption Frequency Index) for different line-outage conditions using Electrical Transient Analyzer Program (ETAP) software. The transmission system comprises 24 load/generation buses that are connected by 38 switches or transformers with two voltages that is, 138 KV and 230 KV. Transmission system data consists of line, transformer, impedance, and reliability data.